Cmv1 is a gate for Cucumber mosaic virus transport from bundle sheath cells to phloem in melon. (6th March 2016) - Guiu‐Aragonés, Cèlia; Sánchez‐Pina, María Amelia; Díaz‐Pendón, Juan Antonio; Peña, Eduardo J.; Heinlein, Manfred; Martín‐Hernández, Ana Montserrat
Summary: Cucumber mosaic virus (CMV) has the broadest host range among plant viruses, causing enormous losses in agriculture. In melon, strains of subgroup II are unable to establish a systemic infection in the near‐isogenic line SC12‐1‐99, which carries the recessive resistance gene cmv1 from the accession PI 161375, cultivar 'Songwhan Charmi'. Strains of subgroup I overcome cmv1 resistance in a manner dependent on the movement protein. We characterized the resistance conferred by cmv1 and established that CMV‐LS (subgroup II) can move from cell to cell up to the veins in the inoculated leaf, but cannot enter the phloem. Immunogold labelling at transmission electron microscopy level showed that CMV‐LS remains restricted to the bundle sheath (BS) cells in the resistant line, and does not invade vascular parenchyma or intermediary cells, whereas, in the susceptible line 'Piel de Sapo' (PS), the virus invades all vein cell types. These observations indicate that the resistant allele of cmv1 restricts systemic infection in a virus strain‐ and cell type‐specific manner by acting as an important gatekeeper for virus progression from BS cells to phloem cells. Graft inoculation experiments showed that CMV‐LS cannot move from the infected PS stock into the resistant cmv1 scion, thus suggesting an additional role for cmv1 related to CMV transport within or exit from the phloem. The characterization of this new form of recessive resistance, based on a restriction of virus systemic movement, opens up the possibility to design alternative approaches for breeding strategies in melon.